Pengaruh Kuliah Daring Terhadap Pemahaman Mahasiswa Tingkat Pertama Pada Mata Kuliah Etika Keperawatan - Edita Revine Siahaan (Ilmiah Institut Citra Internasional, 2021)
The problem of online learning during the Covid 19 pandemic is something that is experienced by all education circles. This was felt by students. The impact of online learning by students is the difficulty of interaction between lecturers and students in the online learning process, student concentration is lacking and student internet network constraints. The purpose of this study was to analyze the effect of online lectures on student understanding of the nursing ethics course at Bunda Delima. Methods: This research design used a quasy experimental design method without a control group with a one group pretest posttest design approach. The population in this study were 50 students. Results: There is a significant difference in the understanding of students before and after being given nursing ethics material between the pretest and posttest with a P value of 0.000 which indicates that the P value is less than 0.05 (<0.05). Conclusion: There is an effect of online lectures on the understanding of first-year students in nursing ethics courses. Suggestion: For further researchers, it is expected that they will take on the problem of online lecture research based on practical applications so that they can see the difference between the problem and online lectures in theory.